Comunidade de espécies espontâneas em uma área de cerrado em restauração ecológica - Toledo Junior, Ari Francisco de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
A technique for restoring degraded areas of the Brazilian savannah is the introduction of native species through the planting of seedlings associated with natural regeneration. The species from natural regeneration constitute the spontaneous plant community in the area under restoration. Our aim was to characterize the composition and structure of the spontaneous woody species community in a Brazilian savannah area under ecological restoration. We conducted a floristic and phytosociological survey, using as inclusion criteria all individuals with height greater than 50 cm. We divide the community into two components, regenerating and remaining. We designate regenerating component, the one formed by woody individuals with stem perimeter at breast height absent or less than 15 cm and remaining component, the one formed by woody individuals with stem perimeter at breast height equal to or greater than 15 cm. We estimated the height and diameter of individuals, indicated the species' habit and dispersal syndrome and determined the phytosociological parameters and Shannon-Wiener diversity and transformed Simpson concentration indices. We found that the community of spontaneous woody species had 159 individuals, belonging to 19 species, of 19 genera and 12 families and a density of 417.3 individuals/ha, with the regenerating component being the most abundant and rich in species. We verified that in the regenerating component the shrubby and anemochoric individuals prevailed and in the remaining component, arboreal and zoochoric individuals. We observed that most of the spontaneous woody species presented height less than 1.5 m and 7 a diameter less than 2 cm. We found an intermediate diversity in the studied community, where few species concentrate the highest values of importance. In the study area, although natural regeneration is slow due to soil compaction, this process of natural regeneration promotes an increase in abundance, richness and ecological complexity in the area under restoration by planting native savannah seedlings.

Uma das técnicas de restauração de áreas degradadas de cerrado consiste na introdução de espécies nativas por meio do plantio de mudas associado à regeneração natural. As espécies que compõem a regeneração natural constituem a comunidade de plantas espontâneas na área em restauração. Nosso objetivo foi caracterizar a composição e a estrutura da comunidade de espécies lenhosas espontâneas em uma área de cerrado em restauração ecológica. Realizamos o levantamento florístico e fitossociológico, utilizando como critério de inclusão todos os indivíduos com altura superior a 50 cm. Dividimos a comunidade como um todo em dois componentes, regenerante e remanescente. Designamos regenerante, o componente formado por indivíduos lenhosos com perímetro do caule à altura do peito ausente ou inferior a 15 cm e remanescente, o componente constituído por indivíduos lenhosos com perímetro do caule igual ou superior a 15 cm. Estimamos a altura e o diâmetro dos indivíduos, indicamos o hábito e a síndrome de dispersão das espécies e determinamos os parâmetros fitossociológicos e os índices de diversidade de Shannon-Wiener e concentração de Simpson transformado. Constatamos que a comunidade de espécies lenhosas espontâneas apresentou 159 indivíduos, pertencentes a 19 espécies, de 19 gêneros e 12 famílias e uma densidade de 417,3 indiv./ha, sendo o componente regenerante o mais abundante e rico em espécies. Verificamos que no componente regenerante prevaleceu os indivíduos arbustivos e anemocóricos e no componente remanescente, os indivíduos arbóreos e zoocóricos. Observamos que a maioria das espécies lenhosas espontâneas apresentou altura inferior a 1,5 m e diâmetro inferior a 2 cm. 6 Constatamos uma diversidade intermediária na comunidade estudada, onde poucas espécies concentram os maiores valores de importância. Na área de estudo, embora a regeneração natural seja lenta, em virtude da compactação do solo, este processo de regeneração natural promove o aumento da abundância, riqueza e complexidade ecológica na área em restauração por plantio de mudas nativas de cerrado.
Community of spontaneous species in a cerrado area in ecological restoration
Keywords: Degraded area; Floristics; Phytosociology; Natural regeneration; Savannah restoration; Área degradada; Florística; Fitossociologia; Regeneração natural; Restauração do cerrado